Pastoral Konseling Anak Korban Keluarga Perselingkuhan di Gereja-gereja Pluit, Jakarta Utara - Citra Ayu Susanto; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
Infidelity in the family has a profound impact on children, especially in the context of the church community. The Pluit area, North Jakarta, which has a number of active churches, is not immune from this problem. Children in the church environment in Pluit may experience feelings of confusion, insecurity, and trauma due to disharmony in their families. The author's reason for raising this theme is in an effort to help children overcome the psychological and spiritual impact of infidelity in the family. A sensitive and holistic pastoral counseling approach plays an important role which aims to explore how children who are victims of infidelity in families at churches in Pluit, North Jakarta. This study used a qualitative approach to literature, literature and field studies in the form of interviews with children who were victims of infidelity at Pluit churches, North Jakarta. The findings from this study provide insight into how pastoral counseling can act as a bridge between the spiritual dimension and psychological support for children who are victims of family infidelity. For the writer this is important because it can encourage the recovery of children and the establishment of a strong spiritual foundation amidst the challenges of modern life.